Multifrequency study of gigahertz‐peaked spectrum sources with RATAN‐600. Issue 9 (2nd November 2021) - Sotnikova, Yulia; Mufakharov, Timur; Mingaliev, Marat; Mikhailov, Alexander
Abstract: We report the radio continuum properties for several samples of peaked spectrum (PS) radio sources. Broadband spectra of the objects were analyzed using the RATAN‐600 six‐frequency (1.2–22 GHz) observations and available literature data, obtained on a time scale of 20–30 years. We discuss statistical differences in radio properties for several AGN types with peaked spectra and focus on PS quasars at high redshifts ( z > 3 ). We confirm that a relatively small fraction (1–2%) of bright PS sources can be considered genuine gigahertz‐peaked spectrums (GPSs) when they have been monitored densely and for a long time. The contamination of GPS source samples by blazars is getting stronger as the redshift increases, and we confirm that it is underestimated due to lack of systematic multifrequency observations.